Hyperglycemia-induced Oxidative Stress and its Role in Diabetes Mellitus Related Cardiovascular Diseases - Vanessa Fiorentino, Teresa; Prioletta, Annamaria; Zuo, Pengou; Folli, Franco (Current Pharmaceutical Design, 2013)
Diabetes mellitus is associated to an increased risk of cardiovascular diseases. Hyperglycemia is an important factor in cardiovascular damage, working through different mechanisms such as activation of protein kinase C, polyol and hexosamine pathways, advanced glycation end products production. All of these pathways, in association to hyperglycemia-induced mitochondrial dysfunction and endoplasmic reticulum stress, promote reactive oxygen species (ROS) accumulation that, in turn, promote cellular damage and contribute to the diabetic complications development and progression. ROS can directly damage lipids, proteins or DNA and modulate intracellular signaling pathways, such as mitogen activated protein kinases and redox sensitive transcription factors causing changes in protein expression and, therefore, irreversible oxidative modifications. Hyperglycemia-induced oxidative stress induces endothelial dysfunction that plays a central role in the pathogenesis of micro- and macro-vascular diseases. It may also increase pro-inflammatory and pro-coagulant factors expression, induce apoptosis and impair nitric oxide release. Oxidative stress induces several phenotypic alterations also in vascular smooth-muscle cell (VSMC). ROS is one of the factors that can promote both VSMC proliferation/migration in atherosclerotic lesions and VSMC apoptosis, which is potentially involved in atherosclerotic plaque instability and rupture. Currently, there are contrasting clinical evidences on the benefits of antioxidant therapies in the prevention/treatment of diabetic cardiovascular complications. Appropriate glycemic control, in which both hypoglycemic and hyperglycemic episodes are reduced, in association to the treatment of dyslipidemia, hypertension, kidney dysfunction and obesity, conditions which are also associated to ROS overproduction, can counteract oxidative stress and, therefore, both microvascular and macrovascular complications of diabetes mellitus.
Keywords: oxidative stress